2016
DOI: 10.1007/s10803-016-2777-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcome for Children Receiving the Early Start Denver Model Before and After 48 Months

Abstract: The Early Start Denver Model (ESDM) is an intervention program recommended for pre-schoolers with autism ages 12-48 months. The rationale for this recommendation is the potential for intervention to affect developmental trajectories during early sensitive periods. We investigated outcomes of 32 children aged 18-48 months and 28 children aged 48-62 months receiving the ESDM for one year (approximately 20 h per week). Younger children achieved superior verbal DQ gains compared to their older counterparts. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
109
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 41 publications
2
109
0
1
Order By: Relevance
“…A logistic analysis further supported that younger age at the beginning of intervention was positively related to greater improvement in ASD severity (OR 5 15, P 5 0.028). Several studies [Howlin, Moss, Savage, & Rutter, 2013;Vivanti et al, 2016] have also reported similar results. However, the age-range of toddlers recruited in our study was relatively small between 18 and 30 months.…”
Section: Insarsupporting
confidence: 64%
See 1 more Smart Citation
“…A logistic analysis further supported that younger age at the beginning of intervention was positively related to greater improvement in ASD severity (OR 5 15, P 5 0.028). Several studies [Howlin, Moss, Savage, & Rutter, 2013;Vivanti et al, 2016] have also reported similar results. However, the age-range of toddlers recruited in our study was relatively small between 18 and 30 months.…”
Section: Insarsupporting
confidence: 64%
“…The positive effect of ESDM has been documented by previous studies [Dawson et al, ; Vismara, Young, & Rogers, ; Rogers et al, ; Vivanti et al, ; Devescovi et al, ; Vivanti, Dissanayake, & Victorian, ; Waddington, van der Meer, & Sigafoos, ; Touzet et al, ]. Reports from the first randomized controlled trial [Dawson et al, ] indicated that ESDM intervention delivered by therapists for 2 years improved cognitive, linguistic, and adaptive behavior and also reduced severity of symptoms of ASD toddlers compared with community interventions, and the gains were maintained 2 years later [Estes et al, ].…”
mentioning
confidence: 73%
“…Encouragingly, communication has been shown to be amongst the most modifiable aspects of adaptive behavior in early intervention trials [e.g., Dawson et al, ; Kasari, Paparella, Freeman, & Jahromi, ; Wetherby et al, ]. However, close examination of findings reveals substantial individual variability in spoken language outcomes in these trials, while community‐based research has revealed that as many as 30% of children receiving early intervention commence school unable to speak in sentences [Norrelgen et al, ; Rose, Trembath, Keen, & Paynter, ; Vivanti, Dissanayake,, & Victorian ASELCC Team, ].…”
Section: Introductionmentioning
confidence: 99%
“…A longterm follow-up study indicated that the children receiving the ESDM intervention maintained gains in their developmental levels and adaptive behaviors 2 years after the intervention with significant reduction in autism symptoms between groups but the diagnostic categorization did not differ (Estes et al, 2015). Eapen et al (2013) also reported significant improvement in autism symptoms in a repeated-measures design; however, some other studies did not find significant change in severity of autism symptoms (Fulton et al, 2014;Vivanti, Dissanayake, & Victorian ASELCC Team, 2016;Vivanti et al, 2013;Vivanti et al, 2014). Overall, findings on the ESDM intervention effects on autism symptoms were mixed across studies.…”
Section: Introductionmentioning
confidence: 99%